Rough Riders : Theodore Roosevelt, his cowboy regiment, and the immortal charge up San Juan Hill /: Theodore Roosevelt, his cowboy regiment, and the immortal charge up San Juan Hill. ([2016]) - Gardner, Mark Lee, 1960-
No abstract available